The new Christianity : or, The religion of the new age - Bland, Salem Goldworth, 1859-1950 (Social history of Canada., 1973)
This volume, a survey of the Canadian scene that urged various reforms, appeared shortly after the First World War. It was considered to be extremely radical in its proposals and implications at that time and had the distinction of being one of that rare breed of attempts to survey Canadian developments in terms of large principles of analysis or historical development. In The New Christianity, Salem Bland tried to place the unrest of the times in a large historical perspective and brought social, political, and economic developments into conjunction with main trends of religion in recent decades. His central theme was that the processes of industrial and social consolidation, the growth of organized labour, and the spread of sociological ideas spelled the end of the old order of capitalism and Protestantism which had dominated most of western Christendom for three centuries. Specifically, the primary impediment to full realization of democracy and brotherhood, Bland argued, was modern capitalism based on private property rights in industry and motivated by a competitive individualism. The second impediment to a new social order embodying the Christian spirit was the strong attachment of Christians to their traditions. The chief hope of the future lay in a marriage of labour Christianity and American Christianity that would unite with all other traditions in a worldwide ecumenical movement. Fifty years later, the reprinting of this book is important because it is an instructive study in how the highest traditions of Christianity came into radical conjunction with the currents of economic change, social reform, and political upheaval in Canada in the first decades of this century.